Profiling the advantaged regions in India from climate and income perspective - Dalwali, Ashok et al (Agricultural Situation in India)
Over the time, our country has made impressive strides in the agriculture sector, form a food deficient country to a food surplus country, primarily based on the technological advancements initiated during the sixties. Despite this laudable progress, economic indicators do not show any impressive growth in the income of the farmers across the states and districts. As per the Doubling Farmers$1 (BIncome (DFI) committee vision the focus must be on accurate demonetization of agriculture produce which must requires an the farmers in timely manner rather than just increasing the agriculture produce. This requires on immediate attention on these double stressed regions having huge untapped potential for transforming the face of Indian agriculture in a real sense. - Reproduceds
Keywords: DFI, Agriculture, Farmers, Climate change, Income, Vulnerable